Myotonia Congenita: Clinical Characteristic and Mutation Spectrum of CLCN1 in Chinese Patients - Hu, Chaoping; Shi, Yiyun; Zhao, Lei; Zhou, Shuizhen; Li, Xihua (Frontiers in Pediatrics, 2021)
Background:CLCN1-related myotonia congenita (MC) is one of the most common forms of non-dystrophic myotonia, in which muscle relaxation is delayed after voluntary or evoked contraction. However, there is limited data of clinical and molecular spectrum of MC patients in China. Patients and Methods: Five patients with myotonia congenita due to mutations in CLCN1 gene were enrolled, which were identified through trio-whole-exome sequencing or panel-based next-generation sequencing test. The clinical presentation, laboratory data, electrophysiological tests, muscular pathology feature, and genetic results were collected and reviewed. We also searched all previously reported cases of MC patients with genetic diagnosis in Chinese populations, and their data were reviewed. Results: The median onset age of five patients was 3.0 years old, ranging from 1.0 to 5.0 years old, while the median age of admit was 5.0 years old, ranging from 3.5 to 8.8 years old. Five patients complained of muscle stiffness when rising from chairs or starting to climb stairs (5/5, 100.0%), four patients complained of delayed relaxation of their hands after forceful grip (4/5, 80.0%), all of which improved with exercise (warm-up phenomenon) (5/5, 100%). Electromyogram was conducted in five patients, which all revealed myotonic change (100%). Genetic tests revealed nine potential disease-causing variants in CLCN1 gene, including two novel variants: c.962T>A (p.V321E) and c.1250A>T (p.E417V). Literature review showed that 43 MC Chinese patients with genetic diagnosis have been reported till now (including our five patients). Forty-seven variants in CLCN1 gene were found, which consisted of 33 missense variants, 6 nonsense variants, 5 frame-shift variants, and 3 splicing variants. Variants in exon 8, 15, 12, and 16 were most prevalent, while the most common variants were c.892G>A (p.A298T) (n = 9), c.139C>T (p.R47W) (n = 3), c.1205C>T(p.A402V) (n = 3), c.1657A>T (p.I553F) (n = 3), c.1679T>C (p.M560T) (n = 3), c.350A>G (p.D117G) (n = 2), c.762C>G (p.C254W) (n = 2), c.782A>G (P.Y261C) (n = 2), and c.1277C>A (p.T426N) (n = 2). Conclusion: Our results reported five CLCN1-related MC patients, which expanded the clinical and genetic spectrum of MC patients in China. Based on literature review, 43MC Chinese patients with genetic diagnosis have been reported till now, and variants in exon eight were most prevalent in Chinese MC patients while c.892G>A (p.A298T) was probably a founder mutation.